A Analisis Penderita Hipertensi Terhadap Laju Filtrasi Glumerolus (LFG) Pada Pasien Yang Menjalani Hemodialisis di RS Banjarmasin - Harun, Lukman (LPPM Universitas Sari Mulia, 2024)
Background : Before experiencing end-stage kidney failure, the sufferer will experience 5 stages as measured by glomerular filtration rate (GFR), namely Stage 1 (GFR above 90), kidney function is still working normally, but early signs of kidney disease may have appeared. Stage 2 (GFR 60–89), kidney function begins to decline slightly. Stage 3 (GFR 30–59), filtering waste substances from the body has begun to become ineffective, so various complaints appear. Stage 4 (GFR 15–29), kidney function is very low. Stage 5/ End Stage Renal Disease (ESDR) (GFR below 15), the kidneys are barely functioning/decreasing, so waste substances and excess fluid accumulate inside so that the body experiences swelling. Objective: This study was to determine the analysis of hypertension sufferers on the glomerular filtration rate in patients undergoing hemodialysis. Method: This type of research is quantitative with an analytical research design with a cross sectional approach. Carried out at one time using a documentation sheet to collect data on respondents with a population in this study of 567 respondents and a sample of 216 respondents, using purposive sampling technique, with chi-square analysis. Result: From this study, the results of the Bivariate analysis of Hypertension sufferers on the Glumerolus Filtration Rate are with a sig value (Pvalue) of 0.006 where the sig value is <0.05 which can be interpreted as meaning that there is a significant relationship between hypertension and the severity of chronic kidney failure, with the OR value 2,282 Conclusion: There is a significant relationship between hypertension and glomerular filtration rate